Quel histórico / [autores, José Luis Gómez Urdáęz, Diego Téllez Alarcia, Francisco Javier Goicolea Julián, Emma Juaneda Ayensa] - Gómez Urdáęz, José LuisTéllez Alarcia, DiegoGoicolea Julián, Francisco JavierJuaneda Ayensa, Emma
En la portada: Universidad de La Rioja-Ayuntamiento de Quel